Epidemiology of injuries in adventure racing athletes. Issue 3 (21st May 2004) - Fordham, S; Garbutt, G; Lopes, P
Abstract : Objectives: To assess the demographics and training characteristics of adventure racing athletes in the United Kingdom, the prevalence and anatomical distribution of hazardous encounter, and overuse injury in this population, and the effects these injuries have on training. Methods: A retrospective training and injury questionnaire for the previous 18 months was distributed to 300 adventure racing athletes at two national race meetings. The definition of an injury was "any musculoskeletal problem causing a stop in training for at least one day, reduction in training mileage, taking of medicine, or seeking of medical aid." Results: The data were derived from the responses of 223 athletes. Advanced level athletes did 11 (4) sessions and 17 (8) hours of training a week (mean (SD)). An injury was reported in the previous 18 months by 73% of the respondents. The most common site of acute injury was the ankle (23%) and of chronic/overuse injury, the knee (30%), followed by the lower back, shin, and Achilles tendon (12% each). There were significant correlations (p<0.01) between the hours spent cycling per week and number of acute injuries, and between the number of days off per week and number of chronic/overuse injuries. Injuries resulted in an average of 23 days training cessation or reduction. Conclusions: Acute injuries were sustained mainly as a result of the nature of the terrain over which athletes train and compete. In overuse injuries lack of adequate rest days was a significant contributing factor. Only a small proportion of training time was spent developing flexibility and core stability.